Postoperative C‐reactive protein concentrations to predict infective complications following gastrectomy for cancer. Issue 7 (5th August 2021) - van Winsen, Marjolein; McSorley, Stephen T.; McLeod, Ross; MacDonald, Andrew; Forshaw, Matthew J.; Shaw, Martin; Puxty, Kathryn
Abstract: Background and Objectives: Gastrectomy for gastric cancer is associated with significant infective postoperative complications. C‐reactive protein (CRP) is a useful biomarker in the early detection of infective complications following major abdominal surgery. This single‐centre retrospective study aimed to determine the relationship between postoperative CRP levels and development of postoperative infective complications after gastrectomy. Methods: Daily postoperative CRP levels were analyzed to determine a CRP threshold associated with infective complications. ROC curve analysis was used to determine which postoperative day (POD) gave the optimal cutoff. Multivariate analysis was performed to determine significant factors associated with complications. Results: One hundred and forty‐four patients were included. A total of 61 patients (42%) had at least one infective complication. A CRP level of 220 mg/L was associated with the highest AUC (0.765) with a sensitivity of 70% and specificity of 76% (positive predictive value, 67%; negative predictive value, 78%). More patients with a CRP > 220 mg/L on POD 3 developed infective complications (67% vs. 21%, p < 0.001). Conclusions: A CRP of more than 220 mg/L on POD 3 may be useful to alert clinicians to the increased risk of a postoperative infective complication or enable earlier safe discharge from critical care for those with a lower value.